Analisis Faktor Preferensi Milenial Bekerja Terhadap Pemilihan Hotel - Lulu Lucyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Some millennials need a comfortable resting place for business trips. The purpose of this study is to analyze what factors influence millennial behavior towards their preferences for choosing hotels during business trips. This study uses a quantitative method with an EFA (Exploratory Factor Analysis) approach with secondary data and primary data stages referring to millennial preference behavior in choosing hotel recommendations. The results of the analysis of millennial behavior factors on preferences for choosing hotels when traveling on business, can show the recommendation of the millennial generation's choice of hotels for business travel needs which refers to millennial behavior towards preferences.